Pengaruh Mutu Pelayanan, Harga dan Promosi terhadap Kepuasan Konsumen di BC Street Coffee Denpasar - I MADE PUTRA AKEN MERTHAYASA; I NYOMAN GEDE USTRIYANA; IGA.A LIES ANGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
The Impact of the Quality of Services, Price and Promotionon the Consumer Satisfaction at BC Street Coffee DenpasarThe annual increase in the contribution made by the trading sector and hotel andrestaurant sector has caused the restaurants in Denpasar, including the BC Street Coffee,to be getting more competitive. It is necessary to analyze the factors, such as the qualityof services, price and promotion, which contribute to the consumer satisfaction. Thiscurrent study is intended to identify the characteristics of the respondents, the quality ofservices, price and promotion on the consumer satisfaction. The study was conductedfrom March to May 2018. The respondents totaled 50. The data were analyzed using thevalidity test, reliability test, multiple linier analysis, classic assumption test, hypothesistest, and descriptive analysis. The dominant consumers of the BC Street Coffee werefrom 18 to 25 years old, male, senior high school graduates, private employees andsingle. They felt highly satisfied with the quality of services, price and promotionprovided. Partially and simultaneously, the quality of services, price and promotionsignificantly contributed to the consumer satisfaction. The R Square showed that thequality of services, price and promotion contributed to the consumer satisfaction by62%, and the rest, namely 38%, was affected by the other variables. It is suggested thatthe BC Street Coffee should always pay attention to what is desired and needed by theconsumers and the price of the product offered. It is suggested to the future researchersthat they add other variables and another object under a particular territory.